Developmentally linked human DNA hypermethylation is associated with down-modulation, repression, and upregulation of transcription. Issue 3 (4th March 2018) - Baribault, Carl; Ehrlich, Kenneth C.; Ponnaluri, V. K. Chaithanya; Pradhan, Sriharsa; Lacey, Michelle; Ehrlich, Melanie
ABSTRACT: DNA methylation can affect tissue-specific gene transcription in ways that are difficult to discern from studies focused on genome-wide analyses of differentially methylated regions (DMRs). To elucidate the variety of associations between differentiation-related DNA hypermethylation and transcription, we used available epigenomic and transcriptomic profiles from 38 human cell/tissue types to focus on such relationships in 94 genes linked to hypermethylated DMRs in myoblasts (Mb). For 19 of the genes, promoter-region hypermethylation in Mb (and often a few heterologous cell types) was associated with gene repression but, importantly, DNA hypermethylation was absent in many other repressed samples. In another 24 genes, DNA hypermethylation overlapped cryptic enhancers or super-enhancers and correlated with down-modulated, but not silenced, gene expression. However, such methylation was absent, surprisingly, in both non-expressing samples and highly expressing samples. This suggests that some genes need DMR hypermethylation to help repress cryptic enhancer chromatin only when they are actively transcribed. For another 11 genes, we found an association between intergenic hypermethylated DMRs and positive expression of the gene in Mb. DNA hypermethylation/transcription correlations similar to those of Mb were evident sometimes in diverse tissues, such as aorta and brain. Our findings have implications for the possible involvement of methylated DNA in Duchenne's muscular dystrophy, congenital heart malformations, and cancer. This epigenomic analysis suggests that DNA methylation is not simply the inevitable consequence of changes in gene expression but, instead, is often an active agent for fine-tuning transcription in association with development.